Android Application for Plants Identification Using Determination Key - Rifai, Muhammad Arif (Proceeding International Conference on Science and Engineering, 2017)
This research aimed at producing application for plant identification using the Android-based determination key and determine the quality of the product application to use as a high school learning support. The study consisted of a preliminary study to identify and capture images of plants from 16 genera of 9 families pteridophyta and 206 genera of 82 families on Spermatophyta. The final result of the product in the form of master Android application with the extension * .APK. Aplikasi rated by one taxonomic expert, one media expert, one information technology expert, 5 peer reviewers, two biology teachers, and tested to 15 students of class X SMA. Overall assessment of the Android application identification of plants shows the percentage of 82.09% votes were included in the excellent qualifications, while the response of students get a percentage rating of 79.82% with good qualifications.